Plasma cell-rich acute rejection of renal allograft: an unusual case of acute allograft dysfunction. (September 2017) - Lee, Kian-Guan; Thangaraju, Sobhana; Ahmed, Syed Salahuddin; Loh, Hwai Liang; Tng, Alvin Ren Kwang; Kee, Terence Yi Shern
We report a case of renal allograft dysfunction due to plasma cell-rich acute rejection (PCAR), which is an uncommon clinical entity with a wide range of differential diagnoses. Extensive diagnostic workup, treatment approach and outcome are discussed and we provide a brief summary of the current management dilemma. Nevertheless, the diagnosis of PCAR portends a poor prognosis and therefore timely diagnosis and intensification of treatment is crucial to prevent disease progression.